Associations of airway tree to lung volume ratio on computed tomography with lung function and symptoms in chronic obstructive pulmonary disease - Tanabe, Naoya; Sato, Susumu; Oguma, Tsuyoshi; Shima, Hiroshi; Sato, Atsuyasu; Muro, Shigeo; Hirai, Toyohiro (Respiratory research, 2019)
Background Decreased airway lumen size and increased lung volume are major structural changes in chronic obstructive pulmonary disease (COPD). However, even though the outer wall of the airways is connected with lung parenchyma and the mechanical properties of the parenchyma affect the behaviour of the airways, little is known about the interactions between airway and lung sizes on lung function and symptoms. The present study examined these effects by establishing a novel computed tomography (CT) index, namely, airway volume percent (AWV%), which was defined as a percentage ratio of the airway tree to lung volume. Methods Inspiratory chest CT, pulmonary function, and COPD Assessment Tests (CAT) were analysed in 147 stable males with COPD. The whole airway tree was automatically segmented, and the percentage ratio of the airway tree volume in the right upper and middle-lower lobes to right lung volume was calculated as the AWV% for right lung. Low attenuation volume % (LAV%), total airway count (TAC), luminal area (Ai), and wall area percent (WA%) were also measured. Results AWV% decreased as the Global Initiative for Chronic Obstructive Lung Disease (GOLD) spirometric grade increased ( p < 0.0001). AWV% was lower in symptomatic (CAT score ≥ 10) subjects than in non-symptomatic subjects ( p = 0.036). AWV% was more closely correlated with forced expiratory volume in 1 s (FEV 1 ) and ratio of residual volume to total lung capacity (RV/TLC) than Ai, Ai to lung volume ratio, and volume of either the lung or the airway tree. Multivariate analyses showed that lower AWV% was associated with lower FEV 1 and higher RV/TLC, independent of LAV%, WA%, and TAC. Conclusions A disproportionally small airway tree with a relatively large lung could lead to airflow obstruction and gas trapping in COPD. AWV% is an easily measured CT biomarker that may elucidate the clinical impacts of the airway-lung interaction in COPD.